2021
DOI: 10.1038/s41430-021-00984-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high-dose parenteral vitamin D3 on COVID-19-related inhospital mortality in critical COVID-19 patients during intensive care unit admission: an observational cohort study

Abstract: BACKGROUND: In many studies, vitamin D has been found to be low in COVID-19 patients. In this study, we aimed to investigate the relationship between clinical course and inhospital mortality with parenteral administration of high-dose vitamin D 3 within the first 24 h of admission to patients who were hospitalized in the intensive care unit (ICU) because of COVID-19 with vitamin D deficiency. METHODS: This study included 175 COVID-19 patients with vitamin D deficiency [25(OH) D <12 ng/mL] who were hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 37 publications
2
60
1
1
Order By: Relevance
“…Considerable discordance exists regarding the effectiveness of Vit D in the treatment of COVID-19, with some reports suggesting a beneficial effect [ 15 , 16 , 17 , 28 , 29 , 31 , 41 , 45 , 53 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] and others no change [ 26 , 27 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 44 , 107 , 108 , 109 ]. The reasons for these disparate findings are likely complex and multifactorial, with varying doses, duration, and timing of Vit D administration along with patient populations and sample sizes all playing roles [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable discordance exists regarding the effectiveness of Vit D in the treatment of COVID-19, with some reports suggesting a beneficial effect [ 15 , 16 , 17 , 28 , 29 , 31 , 41 , 45 , 53 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] and others no change [ 26 , 27 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 44 , 107 , 108 , 109 ]. The reasons for these disparate findings are likely complex and multifactorial, with varying doses, duration, and timing of Vit D administration along with patient populations and sample sizes all playing roles [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D (Vit D) is an oxysterol hormone with important immunomodulatory and antiviral properties [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Even though this vitamin is often recommended as a nutritional supplement in treatment guidelines and prescribed for the management of coronavirus disease 2019 (COVID-19) [ 9 , 10 , 11 , 12 ], several studies have yielded divergent or inconclusive results [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low 25-hydroxy vitamin-D (25-OH D) levels are correlated with high IL-6 levels, and were found to be independent predictors of COVID-19 severity and mortality in the general population [32]. The evidence for the effectiveness of vitamin D supplementation for the prevention and treatment of COVID-19 is, however, very uncertain [33,34]. There was substantial clinical and methodological heterogeneity of the conducted studies, mainly because of different supplementation strategies, formulations, vitamin D status of participants, and reported outcomes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D3 was not administered to the control group. Güven et.al concluded that Vitamin-D3 administration was not associated with improved hospital mortality results [2145].…”
Section: A Vitamin-d Usage In Covid-19 Patientsmentioning
confidence: 99%
“…Conclusively, Guven et.al administered single time higher dosage of 3,00,000 IU, Vitamin-D in Critical COVID-19 patients in ICU [2145] and Murai et.al administered single time higher dosage of 2,00,000 IU, Vitamin-D in moderate to severe COVID-19 patients [2146]. Both of these studies reported no positive outcomes.…”
Section: A Vitamin-d Usage In Covid-19 Patientsmentioning
confidence: 99%